Перспективи використання аморфних Fe–Ni–Si–B стрічок у якості осердя контакторів - Rafiyev, N.M.; Ahmadov, V.I.; Isayeva, A.A. (Publishing house "Academperiodika", 2023)
We consider the possibility to use an amorphous Fe–Ni–Si–B material in the core of contactors, which are widely used in connecting and disconnecting electric circuits, instead of the crystalline material of 3% electric steel. Alloys containing Fe–Ni–Si–B have been treated with the use of mechanical, thermomechanical, and magnetic fields, and the material for practical applications has been obtained. The processing modes were chosen so that a change in the performance of ferromagnetic (below the Curie temperature) alloys during the annealing could be controlled. The obtained specimens were annealed in oil at 360 ∘C in a magnetic field of 200 A/m for 200 min. The temperature mode was chosen so that the stress relaxation could occur during the annealing, and the structural changes in the material could be observed.